Sailing through the COVID-19 Pandemic and Beyond: An Evidence-Based Analysis for Dental Healthcare and Practice - Harpreet Singh; Shabina Sachdeva; Dhirendra Srivastava; Pranav Kapoor; Poonam Sharma; Raj Kumar Maurya; Pinaki Roy (Tehran University of Medical Sciences, 2022)
This integrative review aims to provide a consolidated evidence-based appraisal of the most up-to-date guidelines and recommendations of international public and professional health regulatory bodies in relation to preparedness framework for restructuring safe delivery of dental services amid and beyond the coronavirus disease-2019 (COVID-19) pandemic. Most recent updated guidelines for dental professionals from major international health regulatory bodies were reviewed. PubMed, Google Scholar, Cochrane Central Register of Controlled Trials, WHO COVID-19 and LILACS databases, along with relevant preprints were searched, and citations were checked up to January 23, 2021. The search was performed by one author. Shortlisted articles were read and brought to consensus to be included in the study by at least two co-authors. In case of any disagreement between the judgements, an independent co-author's decision was taken as final. Of 849 records searched, 61 articles were included in the study. Following content analysis of the global guidelines and the collected prevailing evidence, the common themes and recommendations of different guidance documents were collated and summarized into seven domains. Most guidelines have a consensus regarding implementation of rigorous administrative, engineering and environmental infection control strategies. However, variations do exist with regard to the use of respirators in non-aerosol-generating procedure (non-AGP) settings, employment of airborne precautions during non-AGPs, use of supplemental air-handling systems, and preoperative use of mouthwashes. This evidence-based analysis can serve as a useful reopening resource tool and facilitate effective restructuring for delivery of optimal, equitable and safe dental practices globally, during and while emerging from the pandemic.